Pengembangan Multimedia Interaktif Mata Pelajaran Bahasa Arab Materi Profesi Bagi Siswa Kelas VIII SMP IT Al-Huda Wonogiri - Muhammad Luqman Hakim; Asrowi Asrowi; Akhyar Akhyar (JTP - Jurnal Teknologi Pendidikan, 2018)
This research is a Recearch and Development (R&D) by using ASSURE model. The purpose of this research is 1) produce interactive multimedia, which are appropriate with the students’ need 2) to enhance students’ vocabulary of Arabic language. The data were collected by observation, interview, questionnaire, and document. The result of this research is 1) test of media expert showed the product is considered very good, the result is 4.60, 2) expert of the material showed that multimedia interactive is considered good, with result 3,97 3) the test of one to one showed the average score of 4,26 means the product is considered very good, the test of small group evaluation showed the avarage score of 4,38 is considered very good, and the test of field evaluation showed the average score of 4,42 means the product is very good, the conclusion is product can be appliying in learning.